2007
DOI: 10.1590/s0066-782x2007000100008
|View full text |Cite
|
Sign up to set email alerts
|

Exeqüibilidade, segurança e acurácia do ecocardiograma sob estresse com dobutamina/ atropina para detecção de doença arterial coronariana em candidatos a transplante renal

Abstract: Objective: To evaluate the feasibility, safety and accuracy of dobutamine/atropine stress echocardiography (DASE) for the detection of coronary artery disease (CAD) in renal transplant candidates. Methods:Patients candidates to renal transplant were submitted consecutively to DASE and coronary angiography. TheResults: 148 patients underwent the DASE and the coronary angiography. Mean age was 52 ± 9 years, and 69% of the patients were males; 27% had diabetic nephropathy and 73% had LVH; 63% were asymptomatic; 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…[27][28][29][30][31][32][33][34][35] In addition to stress tests, biomarkers such as cardiac troponins in asymptomatic patients with advanced CKD may have prognostic value for risk stratification beyond the traditional use of rising troponins to detect acute coronary syndrome. Persistent elevations in troponin may reflect cardiac stress beyond CAD, such as left ventricular hypertrophy, diastolic dysfunction, and volume overload.…”
Section: Evidence For Screening and Revascularization In Patients Witmentioning
confidence: 99%
See 2 more Smart Citations
“…[27][28][29][30][31][32][33][34][35] In addition to stress tests, biomarkers such as cardiac troponins in asymptomatic patients with advanced CKD may have prognostic value for risk stratification beyond the traditional use of rising troponins to detect acute coronary syndrome. Persistent elevations in troponin may reflect cardiac stress beyond CAD, such as left ventricular hypertrophy, diastolic dysfunction, and volume overload.…”
Section: Evidence For Screening and Revascularization In Patients Witmentioning
confidence: 99%
“…For DSE, estimates for the sensitivity and specificity ranged from 37 to 95% and 71 to 95%, respectively. [27][28][29][30][31] Reported sensitivity and specificity for MPS ranged from 37 to 80% and 37 to 73%, respectively. 29,32,33 In 2011, Wang et al 34 Only two studies had head-to-head comparisons, which seemed to show superior specificity of DSE over MPS and equivalent sensitivity.…”
Section: Evidence For Screening and Revascularization In Kidney Transmentioning
confidence: 99%
See 1 more Smart Citation
“…13 - 18 Even though the use of drugs such stressors has proven safe, recent literature has firmly focused on its complications. 19 - 29 …”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of DSE and MPS varies from 0.44 to 0.89 and 0.29 to 0.92 whereas the specificity of DSE and MPS varies from 0.71 to 0.94 and 0.67 to 0.89, respectively, depending on the type of stress and the number of coronary stenosis>70% [29][30][31][32]. In a meta-analysis of 12 studies involving either thallium-201 MPS or DSE, published in 2003, it was shown that risk of myocardial infarction increased 6 times, and risk of cardiac death increased 4 times in patients with inducible ischemia when compared those without inducible ischemia.…”
Section: Stress Testsmentioning
confidence: 99%